Lexical bias in word recognition by cochlear implant listeners - Gianakas, Steven P. (J Acoust Soc Am, 2019)
When hearing an ambiguous speech sound, listeners show a tendency to perceive it as a phoneme that would complete a real word, rather than completing a nonsense/fake word. For example, a sound that could be heard as either /b/ or /ɡ/ is perceived as /b/ when followed by _ack but perceived as /ɡ/ when followed by “_ap.” Because the target sound is acoustically identical across both environments, this effect demonstrates the influence of top-down lexical processing in speech perception. Degradations in the auditory signal were hypothesized to render speech stimuli more ambiguous, and therefore promote increased lexical bias. Stimuli included three speech continua that varied by spectral cues of varying speeds, including stop formant transitions (fast), fricative spectra (medium), and vowel formants (slow). Stimuli were presented to listeners with cochlear implants (CIs), and also to listeners with normal hearing with clear spectral quality, or with varying amounts of spectral degradation using a noise vocoder. Results indicated an increased lexical bias effect with degraded speech and for CI listeners, for whom the effect size was related to segment duration. This method can probe an individual's reliance on top-down processing even at the level of simple lexical/phonetic perception.